2020
DOI: 10.1186/s40643-020-00348-0
|View full text |Cite
|
Sign up to set email alerts
|

From anaerobic to aerobic treatment: upcycling of digestate as a moisturizing agent for in-vessel composting process

Abstract: In Tunisia, there are crucial challenges facing both urban and rural areas, the most prominent of which are the production of organic waste, the need for waste treatment, the demand for water and energy and the need for a circular economy. To this end, the study was designed to develop a technical concept on closed cycle ‘biowaste to bioenergy’ treating, basically food waste (FW) through combined biological processes. In this approach, the generated digestate from FW anaerobic reactors was used successfully as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…With reference to Casini et al, (2019), the recorded C:N ratio trends might be attributed to the high rate of carbonaceous component consumption during the first five weeks, as well as the lower nitrification rate which was in accordance with the current findings [39]. In the same context, Chaher et al, (2020) reported that a balanced utilization of nitrogenous and carbonaceous elements serves as an efficient indicator to point out the maturity of the end-product which was in line with the identified C:N ratios (at day 37) of both A1 and A2 attaining 12.78 and 14.51, respectively [34].…”
Section: C:n Ratio Profile During the Composting Processsupporting
confidence: 90%
See 1 more Smart Citation
“…With reference to Casini et al, (2019), the recorded C:N ratio trends might be attributed to the high rate of carbonaceous component consumption during the first five weeks, as well as the lower nitrification rate which was in accordance with the current findings [39]. In the same context, Chaher et al, (2020) reported that a balanced utilization of nitrogenous and carbonaceous elements serves as an efficient indicator to point out the maturity of the end-product which was in line with the identified C:N ratios (at day 37) of both A1 and A2 attaining 12.78 and 14.51, respectively [34].…”
Section: C:n Ratio Profile During the Composting Processsupporting
confidence: 90%
“…In fact, MC fluctuations were assigned as an indicator pointing out the need to add further amount of MA. Otherwise, an estimated volume of both fresh water and digestate was determined from the beginning of the process referring to the initial feedstock mixture moisture content and the required MC range [20], [34]. Table 1 displays the trial ingredients and the composting time.…”
Section: Methodsmentioning
confidence: 99%
“…As for the digestate, the BOD 30 to COD ratio is 1:2, indicating that the remaining organics require more adapted biomass and longer retention times for further degradation [14].…”
Section: Biological Oxygen Demandmentioning
confidence: 99%
“…Waste generation is one of the most serious environmental problems facing developing countries globally (Chaher et al, 2020a). Nonetheless, while the anaerobic digestion (AD) of organic waste to biogas is vital to improving energy security, as well as to diversify the energy mix in pursuit of SDG 7, the resulting digestate from the AD process has the potential to be utilized as bio-fertilizer for crop production (SDG 3).…”
Section: Introductionmentioning
confidence: 99%
“…Chaher et al, (2020b) with ve(5) experimental trials as shown in Fig.1.or vegetable waste namely CR, FW, FRW, CR + FW and CR + FW + FRW were respectively co-composted with wood ash and green vegetable waste. The respective ratio of digestate and amendment used are as presented in Table1 Chaher et al, (2020b). with ve (5) experimental trials as shown in Fig.1.…”
mentioning
confidence: 99%